Analysis of selected technological properties of green sands with starch-based additives (Metallurgy and Foundry Engineering, 2015)
The paper presents the results of determination the effect of addition native starch and mineral-starch mixes on selected technological properties of sands. Study was carried out on permeability, compressive strength and wear resistance of molding. Green sand with bentonite and silica sand was compared with green sand with addition Superior Standard native starch or addition of mineral-starch composition in form of binder Albertine F/1.The main difference in applied starch materials is characteristic property of native starch, which is un-soluble in cold water, so in this case it was difficult to bond water added to the moulding sand during mixing of ingredients. However Albertine F/1 starch-based binder is mixture of starch and aluminosilicates, whereby the bonding of water added into moulding sand during ingredients mixing is more efficient.